The hidden burden of female genital schistosomiasis: a cross-sectional study of knowledge, attitudes, and practices in Ghanaian communities - Manyeh, Alfred Kwesi; Ekey, Rosemond Akpene; Kamaldeen, Rukaya Dongu; Fosu, Dorothy; Vidzro, Saviour Edem; Dalaba, Maxwell (Frontiers in Tropical Diseases, 2024)
BackgroundFemale genital schistosomiasis (FGS) is among the most neglected of tropical diseases. FGS remains underreported, under and misdiagnosed and mostly untreated. This neglected epidemic disproportionately affects communities already burdened by HIV and cervical cancer. The study aims to assess FGS knowledge, attitude, and practices and associated factors in communities in the Shai-Osudoku District of Ghana.MethodThe study employed an analytical cross-sectional design, utilizing quantitative methods for data collection from 161 community members. Analysis was conducted using STATA 18, included both descriptive statistics and simple logistic regression.ResultsAbout half (50.31%) of the respondents demonstrated poor knowledge of FGS. Furthermore, 65.84% of the respondents exhibited a poor attitude towards FGS, Poor practice related to FGS were also observed in 60.25% of the respondents. Regression analysis showed significant associations between various factors and knowledge, attitudes, and practices regarding FGS. Specifically, married women were found to have 54% lower odds of possessing good knowledge about FGS compared single women. (AOR=0.46, 95%CI= 0.22-0.94). Respondents with poor socioeconomic status displayed 76% higher odds of engaging in good practices compared to respondents those in the poorest socioeconomic status. (AOR=0.24, 95%CI=0.06-0.96).ConclusionComprehensive, context-specific interventions are necessary to address the multifaceted challenges associated with FGS. Targeted education and awareness campaigns are crucial to improve understanding of FGS, and addressing socio-economic factors that influence attitudes and practices related to the disease is essential.